2018
DOI: 10.2166/wst.2018.379
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic performance of a hybrid anaerobic baffled reactor (HABR): effects of number of chambers, hydraulic retention time, and influent temperature

Abstract: Hydrodynamic performance of a biological reactor is an important design concern since it directly affects the treatment efficiency. In this research, a hybrid anaerobic baffled reactor (HABR) was proposed with improved design concepts and principles. The HABR consisted of a front sedimentation chamber, four regular baffled chambers followed by two floated filter media chambers. The effects of operating variables 5–20 hr hydraulic retention time (HRT) and 10–40 °C of influent temperature, as well as their inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The average VSS/TSS ratio of influent wastewater was 0.55 for HABR (U), and 0.59 for HABR (I) suggested high VSS/TSS ratio for successfully anaerobic digestion [44]. A minor increase (e.g., 4–5%) of TSS or VSS removal was observed in HABR (I) because of insulation, which was perhaps due to ideal intermediate dispersion (e.g., weaker) existed in HABR (I) as suggested from a hydrodynamic study of the HABR [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average VSS/TSS ratio of influent wastewater was 0.55 for HABR (U), and 0.59 for HABR (I) suggested high VSS/TSS ratio for successfully anaerobic digestion [44]. A minor increase (e.g., 4–5%) of TSS or VSS removal was observed in HABR (I) because of insulation, which was perhaps due to ideal intermediate dispersion (e.g., weaker) existed in HABR (I) as suggested from a hydrodynamic study of the HABR [17].…”
Section: Resultsmentioning
confidence: 99%
“…In this research, a hybrid anaerobic baffled reactor (HABR) has been proposed with improved design concepts and principles, which consisted of a front sedimentation chamber, four regular baffled chambers followed by two floated filter media chambers in order to overcome the above-mentioned drawbacks. The recently conducted hydrodynamic study of the proposed HABR configuration has shown that the optimum reactor performance- low dead space (< 10%), excellent hydraulic efficiency (λ > 0.75), and intermediate mixing pattern (Pe > 10)- were achieved using the proposed HABR with more than five chambers [17].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 Differences in HABR and ABR reactor unit designs (Aqaneghad et al, 2017) HABR technology also uses a reactor that has several separators, but the reactor used in this technology is a combination of a suspended reactor and an attached reactor (Aqaneghad et al Aqaneghad et al, (2017), Khalekuzzaman et al, (2018) and Khalekuzzaman et al, (2019). Research conducted by Aqaneghad et al, (2017) concluded that the way HABR works is the same as ABR.…”
Section: Introductionmentioning
confidence: 99%
“…Aqaneghad et al, (2017) drained wastewater into a reactor unit with 5 compartments, which were divided into a suspended reactor in the initial compartment and 4 attached reactor compartments filled with media and succeeded in reducing the pollutant load of total BOD and phosphate levels by 94.5% and 30.2%. Khalekuzzaman et al, (2018) stated that the more the number of compartments, the higher the efficiency of HABR performance. Research conducted by Khalekuzzaman et al, (2018) with the HABR design consisting of 7 compartments resulted in a more optimum reactor performance compared to 5 compartments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation